Optimizing Work-Life Equilibrium: A Case Study of Work-Life Balance Strategies and Employee Well-Being at Brain Academy (Ruangguru) - Yeti, Yeti (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to investigate the effect of implementing work-life balance strategies on employee well-being in an organizational context. A quantitative approach with multiple regression analysis was used to analyze data from surveys conducted on employees. Findings show that flexibility of working hours, flexible leave policies, remote work, accessibility of health and wellness facilities, and work-life balance programs significantly contribute to employee well-being. The implication of these findings is that it is important for companies to pay attention to these aspects in designing their human resource management policies and practices to improve employee welfare and productivity.